The Effect of Solar Irradiance on Innovative‎ Autoclave Operated by Solar Energy - Saleh, Nada S.; Hussain, Hazim H. (Iraqi Journal of Science, 2024)
An autoclave is a device for sterilizing medical and surgical tools in hospitals and healthcare centers. The lack of electric power supply in some hospitals and rural health centers, in addition to pollution caused by fossil fuels, reinforces the need to search for other energy sources to operate the autoclave. Solar autoclaves can be utilized as an alternative choice in such circumstances. This work describes the effectiveness of the solar-powered autoclave, which is used for wet sterilization. The device is designed from a parabolic dish reflector covered with mirrors that reflect solar radiation toward the center of a focus for heating a vessel. It was found that the highest value of the average energy efficiency was 19 % and the average exergy efficiency was 2 % at 9:00 am and the lowest value of the average energy efficiency was 1.5% and the average exergy efficiency was 0.4 % at 12:00 noon. The effectiveness was tested against (pseudomonas aeruginosa) bacteria, where the highest values of steam temperatures for sterilization were recorded between 121 °C to 122 °C. It was also found that the sterilization efficiency was 100 % under steam pressure of 1.18 bar for every 30 minutes of the sterilization cycle for the periods 11:00 am to 11:30 am, 11:30 am to 12:00 noon, and 12:00 noon to 12:30 pm).